1989
DOI: 10.1002/btpr.5420050309
|View full text |Cite
|
Sign up to set email alerts
|

Phase Partitioning of Biomolecules: Solubilities of Amino Acids

Abstract: The representation of phase equilibrium for amino acids, peptides, and proteins in solution is an important problem in the design and optimization of downstream processes for recovery of the biomolecules. This paper presents a molecular thermodynamic framework [1, 2] for the representation of the solubilities of amino acids and small peptides. With this framework, satisfactory results have been obtained in representing and predicting the solubilities of amino acids and small peptides in aqueous solution as fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(95 citation statements)
references
References 13 publications
1
94
0
Order By: Relevance
“…The number of estimated parameters varies from 3 to 10. Chen et al (1989) added two different contributions for the calculation of the excess Gibbs energy of the system: one is the result of the long-range interactions and was represented by a Pitzer-DebyeHuckel term (Pitzer, 1980); the other is due to local interactions and was formulated by a modified form of the NRTL equation (Renon and Prausnitz, 1968) with two adjustable energy parameters for each amino acidJwater pair. As the data were correlated, each amino acid separately, the results were very satisfactory, both for correlation of activity coefficients (mean deviation of 2 % ) and of solubilities (mean deviation < 1.8%).…”
Section: Introductionmentioning
confidence: 99%
“…The number of estimated parameters varies from 3 to 10. Chen et al (1989) added two different contributions for the calculation of the excess Gibbs energy of the system: one is the result of the long-range interactions and was represented by a Pitzer-DebyeHuckel term (Pitzer, 1980); the other is due to local interactions and was formulated by a modified form of the NRTL equation (Renon and Prausnitz, 1968) with two adjustable energy parameters for each amino acidJwater pair. As the data were correlated, each amino acid separately, the results were very satisfactory, both for correlation of activity coefficients (mean deviation of 2 % ) and of solubilities (mean deviation < 1.8%).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, chemical analyses suggest that the protein-like fluorophores consist primarily of proteinaceous materials (e.g., proteins and peptides; Yamashita and Tanoue, 2003;Maie et al, 2007), and this DOC fraction is generally hydrophilic and low molecular weight (LMW) compounds (e.g., Sommerville and Preston, 2001). Results of Chen et al (1989) and Fuchs et al (2006) showed that solubility of the proteinaceous materials in LMW is generally affected by neither pH within the normal range of 6-9 nor colloid coagulation. Therefore, increasing ionic strength (or salinization) can enhance the solubility of the proteinaceous materials via sodium dispersion (Green et al, 2008(Green et al, , 2009a or through nonspecific electrostatic interactions at low salinities (called a "salting-in" effect) (Tanford, 1961;Chen et al, 1989).…”
Section: S Duan and S S Kaushal: Salinization Alters Fluxes Of Biomentioning
confidence: 96%
“…Results of Chen et al (1989) and Fuchs et al (2006) showed that solubility of the proteinaceous materials in LMW is generally affected by neither pH within the normal range of 6-9 nor colloid coagulation. Therefore, increasing ionic strength (or salinization) can enhance the solubility of the proteinaceous materials via sodium dispersion (Green et al, 2008(Green et al, , 2009a or through nonspecific electrostatic interactions at low salinities (called a "salting-in" effect) (Tanford, 1961;Chen et al, 1989). Furthermore, because stream sediments are generally enriched in these labile, proteinaceous materials derived from biofilms (algae and microbes) and wastewater organics in urban watersheds (Daniel et al, 2002;Kaushal et al, 2011Kaushal et al, , 2014bKaushal and Belt, 2012;Newcomer et al, 2012;, it is reasonable that salinization can mobilize a large amount of protein-like labile dissolved organic matter from stream sediments.…”
Section: S Duan and S S Kaushal: Salinization Alters Fluxes Of Biomentioning
confidence: 96%
“…There are two main groups of models: (i) those which consider that the amino acid dissociation gives rise to charged species in solution, and take account of long-range forces using a Debye-Hückel term (UNIQUAC model by Peres and Macedo [24], UNIFAC group-contribution method by Pinho et al [25]); (ii) those which do not consider the long-range interactions, as the amino acid in pure water is mainly in zwitterionic form {nonrandom two-liquid (NRTL) equation by Chen et al [26], UNIFAC method by Kuramochi [27], modified Wilson equation by Xu et al [28]}. The results obtained are all very satisfactory, being the modified Wilson equation [28] and the UNIQUAC method E. A. MACEDO [24] those giving the better predictions.…”
Section: Modelingmentioning
confidence: 99%